Pengaruh Partisipasi Anggaran terhadap Budgetary Slack dengan Motivasi dan Komitmen Organisasi sebagai Pemoderasi - Wahyu Puteri Dinanti; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to determine the effect of budgetary participation on budgetary slack moderated by organizational motivation and commitment. This research was conducted in the regional organization Limapuluh Kota Regency. Respondents used in the study were the Head of OPD, Head of Finance and employees who play a role in the budgeting process, with a total of 93 respondents. Sample selection was done by using purposive sampling method. Data collection was done through a questionnaire. The analytical technique used in this research is Moderated Regression Analysis with IBM SPSS 25 software for windows. From the simple regression results, it produces one hypothesis that shows its effect on budgetary slack, namely: 1) budget participation has a positive and significant effect on budgetary slack. Meanwhile, the results of the moderating regression analysis show two hypotheses that have no effect on budgetary slack, namely: 2) the interaction between budgetary participation and motivation has a negative and insignificant effect on budgetary slack. 3) the interaction between budget participation and organizational commitment has a positive and no significant effect on budgetary slack.